Family Roles in Referral Decision-Making for Maternal-Neonatal Emergency Cases: A Phenomenological Study - Rafhani Rosyidah (International Journal on Orange Technologies, 2026)
Maternal-neonatal emergencies require rapid decision-making and timely referral to prevent poor outcomes for mothers and newborns. However, referral decisions are often influenced not only by health care providers but also by family members who hold authority, provide resources, and give permission during emergencies. This study aimed to explore family roles in referral decision-making for maternal-neonatal emergency cases. This study used a qualitative design with a phenomenological approach. Ten family members who had been directly involved in referral decision-making during maternal or neonatal emergency situations were selected through purposive sampling. Data were collected using in-depth, semi-structured interviews supported by field notes. Interview recordings were transcribed verbatim and analyzed using thematic analysis. Trustworthiness was maintained through credibility, transferability, dependability, and confirmability. Four main themes emerged from the analysis: family authority in referral decision-making, recognition of emergency conditions, barriers to timely referral, and trust in health care providers. Husbands, parents, and in-laws often influenced approval or delay of referral. Families who recognized danger signs tended to accept referral more quickly, while limited knowledge, financial concerns, transportation difficulties, distance, and the need for family discussion contributed to delays. Clear communication and reassurance from health care providers strengthened family trust and supported faster referral decisions. Family roles in maternal-neonatal emergency referral are complex and multidimensional. Strengthening family-centered education, effective provider communication, and referral preparedness is essential to improve timely decision-making and support better maternal-neonatal outcomes.